Remote Sensing applied to the analysis of the phenomenon of Urban Heat Islands in the City of Vitória, Espírito Santo - Barboza, Eliezio Nascimento (2020)
The increasing development of cities without proper environmental and urban planning has resulted in the increase in temperature in large cities. One of the main phenomena caused by this warming are the so-called urban heat islands, which interfere with the local climate and thermal comfort. In addition to other factors, the poor distribution of green areas in the city contributes to the increase of this phenomenon. Therefore, the objective of this article is to analyze the Earth's Surface Temperature (TST) and relate with vegetation cover through the Normalized Difference Vegetation Index (NDVI) in the city of Vitória, ES. Initially, orbital images, OLI (Operational Land Imager) and TIRS10 (Thermal Infrared Sensor) of Landsat 8 were obited in the United States Geological Survey (USGS) – orbit 215 and point 74. The images chosen for this study are from 16/05/2013. It was verified the direct relationship of biomass vigor (NDVI) and urbanization with surface temperature values and urban heat islands in the city of Vitória. The environments with the lowest NDVI values, except for the ocean, presented higher temperature values, exposing the importance of vegetation for the urban climate.